Electrochemical nanoporous alumina membrane-based label-free DNA biosensor for the detection of Legionella sp - Rai, Varun (2013)
An electrochemical nanoporous alumina membrane-based label free DNA biosensor is developed using 5′-aminated DNA probes immobilized into the nanochannels of alumina. Alumina nanoporous membrane-like structure is carved over platinum wire electrode of 76 μm diameter dimension by electrochemical anodization. The hybridization of complementary target DNA with probe DNA molecules attached inside the nanochannels influences the pore size and ionic conductivity. Electrochemical biosensing signal is derived from only redox species Fe(CN)64− across single wire Pt electrode. The biosensors sensing mechanism relies on the monitoring of electrode's Faradaic current response toward redox species, Fe(CN)64−, which is sensitive toward the hybridization of complementary target with probe DNA immobilized into the alumina nanochannels. The biosensor demonstrates wide linear range over 7 orders of magnitude with ultrasensitive detection limit 3.1×10−13 M for the quantification of ss 21mer DNA sequence and selectively differentiates the complementary sequence from target sequences with single base mismatch (MM1) and triple bases mismatch (MM3) of different strain of Legionella sp. Its applicability is also challenged against real time Legionella pneumophila genomic DNA sample derived from the asymmetric PCR method.